Microstructure and properties of ablative C/ZrC–SiC composites prepared by reactive melt infiltration of zirconium and vapour silicon infiltration. Issue 3 (15th February 2017) - Chen, Si'an; Li, Guangde; Hu, Haifeng; Li, Yong; Mei, Min
Abstract: C/ZrC-SiC composites with a density of 3.09 g/cm 3 and a porosity of 4.8% were prepared by reactive melt infiltration and vapour silicon infiltration. The flexural strength and modulus were 235 MPa and 18.3 GPa, respectively, and the fracture toughness was 7.0 MPa m 1/2 . The formation of SiC and ZrSi2 during vapour silicon infiltration, at the residual cracks and pores in the C/ZrC, enhanced the interface strength and its mechanical properties. The high flexural strength (223 MPa, c . 95% of the original value) after oxidation at 1600 °C for 10 min indicated the excellent oxidation resistance of the composites after vapour silicon infiltration. The mass loss and linear recession rate of the composites were 0.0071 g/s and 0.0047 mm/s, respectively and a fine ablation morphology was obtained.